Performance Measurement of Corporate Tax Departments - Robinson, John R.; Sikes, Stephanie A.; Weaver, Connie D. (The Accounting Review, 2010)
ABSTRACT: We investigate why firms choose to evaluate a tax department as a profit center (“contributor to the bottom line”) as opposed to as a cost center and the association between this choice and effective tax rates (ETRs). Using data from a confidential survey taken in 1999 of Chief Financial Officers, we develop and test a theory for choosing between these two methods of evaluating a tax department. We find that the likelihood of evaluating the tax department as a profit center is increasing in firm decentralization characteristics and tax-planning opportunities. We then employ instrumental variables to investigate whether evaluating a tax department as a profit center provides an effective incentive for the tax department to contribute to net income through lower ETRs. We find that our instrument for profit center firms is associated with significantly lower ETRs than cost center firms.